A Study of EFL Students' Cultural Empathy from Cross-Cultural Communication Perspective - Siti Hajar Amrina; Lilia Indriani (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Cultural empathy is an essential thing in cross-cultural communication, which is a complex unit in teaching foreign languages. Empathy plays a crucial role in placing oneself concerning the views of others. Briefly, (Matthew, 2003) stated, Empathy Pedagogy applied the theory of empathy to language teaching and appealed educators to pay more attention to the teaching system that can help students cultivate the ability of cross-cultural communication. The objectives of this study are to investigate the relationship between cultural empathy and cross-cultural communication to create an effective method of learning English as a foreign language. This research uses a descriptive quantitative method. To accomplish this objective, this study conducted interviews with 39 students of English Education, Tidar University. The result of the research shows that there is a positive relationship between cultural empathy and cross-cultural communication. That way, it is necessary to have an appropriate method in learning English as a foreign language.